Erlotinib added to carboplatin and paclitaxel as first-line treatment of ovarian cancer: A phase II study based on surgical reassessment - Blank, Stephanie V.; Christos, Paul; Curtin, John P.; Goldman, Noah; Runowicz, Carolyn D.; Sparano, Joseph A.; Liebes, Leonard; Chen, Helen X.; Muggia, Franco M. (Gynecologic oncology, 2010)
The purpose of this study was to determine whether adding the anti-epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor erlotinib to carboplatin/paclitaxel improved pathologic complete response (pCR) at reassessment surgery in epithelial ovarian, fallopian tube, or primary peritoneal cancers (OFPC). Patients with stage III–IV OFPC initiated treatment within 12 weeks of initial cytoreductive surgery or, after histologic confirmation of diagnosis, neoadjuvantly. Treatment included paclitaxel (175 mg/m 2) and carboplatin (AUC 6) every 3 weeks for up to 6 cycles, plus oral erlotinib 150 mg daily. The primary objective was to determine whether the pCR rate at reassessment surgery was at least 60% after optimal cytoreduction at initial surgery (< 1 cm residual disease), or at least 40% after suboptimal cytoreduction (at least 1 cm residual disease) using a two-stage design (alpha = 0.10, beta = 0.10). The study population included 56 patients with stage III-IV OFPC. EGFR gene amplification was present in 15% of the 20 tumors evaluated. Twenty-eight patients had protocol therapy after optimal cytoreduction (stratum I), 23 had protocol therapy either after suboptimal cytoreduction (stratum II), and 5 received neoadjuvant therapy prior to cytoreduction (stratum III). Pathologic CR was confirmed in 8 patients (29%; 95% confidence intervals 13%, 49%) in stratum I and 3 patients (11%, 95% C.I. 2%, 28%) in stratum II, which did not meet the prespecified efficacy endpoint in either stratum. Among unselected patients, erlotinib plus carboplatin-paclitaxel did not improve pCR rates compared with historical experience with carboplatin-paclitaxel alone in patients with stage III–IV OFPC.